Identity, Community, and Sexuality in Slash Fan Fiction Pocket Publics - Kustritz, Anne (Routledge Advances in Fan and Fandom Studies, 2024)
slash fan fiction, digital circulation, queer represenation, women, community space, cultural studies, law,